A Novel Derivative of (-)mycousnine Produced by the Endophytic Fungus Mycosphaerella nawae, Exhibits High and Selective Immunosuppressive Activity on T Cells - Wang, Li-Wei; Wang, Jin-Liang; Chen, Jing; Chen, Jia-Jie; Shen, Jia-Wei; Feng, Xiao-Xiao; Kubicek, Christian P.; Lin, Fu-Cheng; Zhang, Chu-Long; Chen, Feng-Yang (Frontiers in Microbiology, 2017)
An endophytic fungus, Mycosphaerella nawae ZJLQ129, was isolated from the leaves of the traditional Chinese medicine Smilax china. From the fermentation broth and mycelium, a dibenzofurane compound (-)mycousnine (1) was isolated. Chemical modification of it to the amide derivative (-)mycousnine enamine (2), which is new to science, was found to have high and selective immunosuppressive activity: similar to cyclosporin A, (-)mycousnine enamine (2) selectively inhibited T cell proliferation, suppressed the expression of the surface activation antigens CD25 and CD69 and the formation and expression of the cytokines interleukin-2 as well as interferon γ in activated T cells, but did not show any effect on the proliferation of B cells and cancer cells (PANC-1 and A549) and the activation of macrophages. Furthermore, the cytotoxicity of (-)mycousnine enamine was lower than that of cyclosporin A, and its therapeutic index (TC50/ EC50) was 4463.5, which is fivefold higher than that of cyclosporin A. We conclude that (-)mycousnine enamine (2), the semi-synthestic product prepared from the native product (-)mycousnine (1) of the endophyte M. nawae is a novel effective immunosuppressant showing low toxicity and high selectivity.